Baculoviral inhibitor of apoptosis family of proteins repeat-containing 5 gene methylation status in peripheral blood mononuclear cells and plasma survivin levels in patients with Behçet’s disease - Yasamin PAHLAVAN,; Alireza KHABBAZI, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the baculoviral inhibitor of apoptosis repeat-containing 5 (BIRC5) gene methylation in the peripheral blood mononuclear cells (PBMCs) in patients with Behçet’s disease (BD) compared to healthy controls and the association of survivin with BD activity. Patients and methods: A cross-sectional study was conducted on 43 BD patients (22 males, 21 females; mean age 36.6±10.1 years; range, 18 to 66 years) and 44 age- and sex-matched healthy controls (23 males, 21 females; mean age 35.4±7.5 years; range, 18 to 61 years) between August 2019 and December 2019. Sample size was calculated guided by taking into account the difference of 1.5 units between the mean expression of BIRC5 gene in the BD and control groups, as well as considering α=0.5 and power=80%. We assessed the methylation status of the BIRC5 gene in PBMCs of BD and control groups by methylation-specific polymerase chain reaction (MS-PCR). Plasma levels of survivin were measured by enzyme- linked immunosorbent assay. Results: Oral aphthous ulcer, genital ulcer, and skin lesions were the most common clinical manifestations in BD group. MS-PCR showed that the deoxyribonucleic acid samples of BD and control groups were not different in methylated and unmethylated areas and alleles were heterozygote. No significant difference was observed in the plasma levels of survivin in BD (98.86±25.5 pg/mL) and control (118.16±37.4 pg/mL) groups. There was no significant correlation between survivin plasma levels and BD activity. Conclusion: Our study did not show any evidence of association between the alteration in the BIRC5 gene methylation, survivin production, and apoptosis dysregulation in BD.